If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + 3x = 91 Solving 15 + 3x = 91 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 3x = 91 + -15 Combine like terms: 15 + -15 = 0 0 + 3x = 91 + -15 3x = 91 + -15 Combine like terms: 91 + -15 = 76 3x = 76 Divide each side by '3'. x = 25.33333333 Simplifying x = 25.33333333
| 6n-9=3-n+3n | | 2y-y=-5 | | 3x-5=2(3y+6) | | -8+5n=7n+2 | | 3/5x-1/3y=-4 | | -6+6n=1+5n | | 9.1-12.9= | | -5(4p-5)=4p+25 | | -12[x+5]=144 | | 6(1-5n)=-3(n-2) | | 2(x+3y)=4(x-y)+5 | | -4+4(1-7v)=6v+34 | | -4+4(1-7v)=6v | | x+10y=209 | | 6-30n=-3n-2 | | -3x+5=6x+7(4x+1) | | (0.3x^4)(-0.8x^6)= | | 6-30n=-3-2 | | -6k+27=3(6-5k) | | 5(5r+8)=8r-28 | | -(k-1)=1-3k | | -6(x+1)=-13+x | | 10+6x-4x=-3x-5 | | x^5+4x^4-17x^3-60x^2=0 | | -3p+4=-20 | | N+28=-4 | | -6+2b=6+6b | | -4(a-2b)+3(5-a)=4 | | -11-4v=-1-2v | | 2/5w-15=6/5 | | 1-2(7x+3)=-3(4+7x) | | -4m-5m=-5-4m |